Feeding the Global VAR with theory: Is German wage moderation to blame for European imbalances? - Timo Bettendorf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyses the importance of German wage moderation in the context of European imbalances. Using information from a New Keynesian small open economy model with labor market frictions, we derive sign restrictions for a wage markup shock. This information enables us to identify a German wage markup shock by imposing restrictions on the impulse response functions of German variables in a Global VAR model. We find that negative German wage markup shocks do generally cause an improvement of the domestic trade balance and a deterioration of foreign trade balances in the Euro Area. However, they account only for a limited proportion of trade balance forecast error variances. Hence, German wage moderation cannot be the lone driver of European imbalances.
Keywords: F41; F32; F10; 330